Effect of steam blanching on lycopene and total phenolics in pink guava puree industry by-products - Kong, Kin Weng; Khairul Ikram, Emmy Hainida; Othman, Azizah; Ismail, Amin; Tan, Chin Ping (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Lycopene and total phenolics of pink guava puree industry by-products (refiner, siever and decanter) were evaluated after steam blanching at selected temperatures and times. Lycopene content was in the order of decanter > siever > refiner (7.3, 6.3 and 1.5 mg/100 g, respectively), and the content of total phenolics was in the order of refiner > siever > decanter (4434.1, 2881.3 and 1529.3 mg GAE/100 g, respectively). Regression coefficients for temperatures (x1) and times (x2) from multiple linear regression models of siever and decanter showed significant (p<0.05) negative relationships with lycopene (y1) and total phenolics (y2). Nevertheless, lycopene content in decanter increased significantly about 13% from the control when steam blanching at 60 °C for 20-60 min. More than 27% of total phenolics were lost in blanched refiner. Regression analysis revealed the increasing loss of lycopene and total phenolics during steam blanching could occur when increasing in temperature and time.